Polimorfismo cromosómico intraespecífico en la serpiente de coral Micrurus nigrocinctus (Ophidia: Elapidae) - Guitérrez, José María (1981)
Two principal karyological patterns were observed in 59 coral snakes (Micrurus nigrocinctus) from Costa Rica: I, "nigrocinctus" (2n = 26) and II "mosquitensis '" (2n =30), which correspond to the subspecies M. n. nigrocinctus and M. n. mosquitensis, respectively. These chromosomal patterns differ in the number of microchromosomes and in the position of the centromere in the eighth pair of macrochromosomes. In the M. n. nigrocinctus group we found three specimens with an additional microchromosome (2n =27) and one with two more (2n = 28). Among the M. n. mosquitensis we saw two individuals with a variation in the position of the centromere in the W chromosome. This study confirm s the intraspecific chromosomal polimorphism characteristic of this species.